7.1 kW coherent beam combining system based on a seven-channel fiber amplifier array. (August 2021) - Ma, Pengfei; Chang, Hongxiang; Ma, Yanxing; Su, Rongtao; Qi, Yunfeng; Wu, Jian; Li, Can; Long, Jinhu; Lai, Wenchang; Chang, Qi; Hou, Tianyue; Zhou, Pu; et al.
Highlights: Coherent combination of 7-channel kW-level all-fiber amplifiers has been achieved. The total output power of the beam combining system is ~7.1 kW. First time compensate phase noise in 7-channel kW fiber amplifiers by SPGD algorithm. Abstract: Coherently combining of seven-channel narrow-linewidth, linear-polarized, kW-level power all-fiber amplifiers has been successfully demonstrated by using the stochastic parallel gradient descent (SPGD) algorithm. The seven polarization-maintained fiber amplifiers are tiled by a collimator array with a high lenslet filling factor (~95%). Total emitting power is ~8 kW, and ~7.1 kW combined output power is achieved and the contrast of the far-field intensity pattern is measured to be ~86% when the system is in the closed loop. This work could provide practical reference on scaling the output power of the tiled aperture coherent beam combining system.